ADAR1-mediated regulation of melanoma invasion - Yael Nemlich (Nature Portfolio, 2018)
In metastatic melanoma, ADAR1 is downregulated, facilitating proliferation. Here, the authors show an ADAR1-dependent and RNA-editing-independent regulation of melanoma invasion mediated by ITGB3 expression, which can be reversed when ITGB3 is blocked.